Whole Body Interaction - England, David (Human-Computer Interaction Series,, 2011)
Whole Body Interaction is "The integrated capture and processing of human signals from physical, physiological, cognitive and emotional sources to generate feedback to those sources for interaction in a digital environment" (England 2009). Whole Body Interaction looks at the challenges of Whole Body Interaction from the perspectives of design, engineering and research methods. How do we take physical motion, cognition, physiology, emotion and social context to push boundaries of Human Computer Interaction to involve the complete set of human capabilities? Through the use of various applications the authors attempt to answer this question and set a research agenda for future work. Aimed at students and researchers who are looking for new project ideas or to extend their existing work with new dimensions of interaction.